Stereoselective Phosphorylation of Cyclopropavir by pUL97 and Competitive Inhibition by Maribavir - Gentry, Brian G. (American Society for Microbiology (ASM), 2010)
Human cytomegalovirus (HCMV) is a widespread pathogen that can cause severe disease in immunologically immature and immunocompromised individuals. Cyclopropavir (CPV) is a guanine nucleoside analog active against human and murine cytomegaloviruses in cell culture and efficacious in mice by oral administration. Previous studies established that the mechanism of action of CPV involves inhibition of viral DNA synthesis. Based upon this action and the structural similarity of CPV to ganciclovir (GCV), we hypothesized that CPV must be phosphorylated to a triphosphate to inhibit HCMV DNA synthesis and that pUL97 is the enzyme responsible for the initial phosphorylation of CPV to a monophosphate (CPV-MP). We found that purified pUL97 phosphorylated CPV 45-fold more extensively than GCV, a known pUL97 substrate and the current standard of treatment for HCMV infections. Kinetic studies with CPV as the substrate for pUL97 demonstrated a K(m) of 1,750 ± 210 μM. Introduction of 1.0 or 10 nM maribavir, a known pUL97 inhibitor, and subsequent Lineweaver-Burk analysis demonstrated competitive inhibition of CPV phosphorylation, with a K(i) of 3.0 ± 0.3 nM. Incubation of CPV with pUL97 combined with GMP kinase [known to preferentially phosphorylate the (+)-enantiomer of CPV-MP] established that pUL97 stereoselectively phosphorylates CPV to its (+)-monophosphate. These results elucidate the mechanism of CPV phosphorylation and help explain its selective antiviral action.